Clinical outcomes in donors and recipients of kidney transplantations involving medically complex living donors – a retrospective study. (29th July 2020) - Kinoshita, Yoshitaka; Yagisawa, Takashi; Sugihara, Toru; Hara, Konan; Takeshima, Saki; Kubo, Taro; Shinzato, Takahiro; Shimizu, Toshihiro; Suzuki, Michiko; Maeshima, Akito; Kamei, Jun; Fujisaki, Akira; et al.
Summary: We retrospectively compared the post‐transplantation graft survival and the donor's estimated glomerular filtration rates (eGFRs) following living donor kidney transplantations (LDKTs) involving medically complex living donors (MCLDs) (the elderly and patients with obesity, hypertension, diabetes mellitus, or reduced renal function) and standard living donors (SLDs). The clinical data on patients who underwent LDKTs at our institution from 2006–2019, including 192 SLDs and 99 MCLDs, were evaluated. Regarding recipients, the log‐rank test and multivariable Cox proportional hazards analyses showed a higher incidence of overall and death‐censored graft loss in the recipients who received kidneys from MCLDs (Hazard ratio = 2.16 and 3.25, P  = 0.015 and 0.004, respectively), after adjusting for recipient‐related variables including age, sex, duration of dialysis, ABO compatibility, and donor‐specific antibody positivity. Regarding donors, a linear mixed model showed significantly lower postdonation eGFRs (−2.25 ml/min/1.73 m 2, P  = 0.048) at baseline in MCLDs than SLDs, but comparable change (difference = 0.01 ml/min/1.73 m 2 /year, P  = 0.97). In conclusion, although kidneys from MCLDs are associated with impaired graft survival, the donation did not adversely affect the MCLDs' renal health in at least the short‐term. LDKTs involving carefully selected MCLDs would be an acceptable alternative for recipients with no SLDs.